Jingjiao the Church of the East in China and Central Asia - Malek, Roman 1951-2019; Hofrichter, Peter 1940- (Collectanea Serica, 2022)
"The contributions in this volume were mostly first presented at the conference "Research on Nestorianism in China. Zhongguo jingjiao yanjiu" held in Salzburg, 20- 26 May 2003. Like the conference, the volume explores the subject of "Nestorianism" (jingjiao, "Luminous Religion") in a variety of aspects. The material of the present collection is organized in five parts. The first part presents different aspects of the past and current research on jingjiao. The second part discusses jingjiao in the Tang dynasty, especially the question of the "Nestorian" texts and documents, their authenticity and theology. The third part deals with the "Nestorian" inscriptions and remains from the Yuan dynasty, especially from Quanzhou. Part four is dedicated to questions of the Church of the East in Central Asia and other historically relevant countries. The last part of the book presents a "Preliminary Bibliography on the Church of the East in China and Central Asia" prepared especially for this volume"--